Eating disorders: Do PET and SPECT have a role? A systematic review of the literature. (30th June 2020) - Gianni, Angela Di; De Donatis, Domenico; Valente, Stefano; De Ronchi, Diana; Atti, Anna Rita
Highlights: PET and SPECT have a role in understanding the neurobiology of eating disorders. Density of serotonin receptor 1A is increased in both affected and recovered patients. Serotonin transporter binding is increased or diminished in specific cortical areas. Dopamine is blunted in the putamen of Bulimia Nervosa such as in substance abusers. SPECT studies suggest a cingulate-temporal cortical dysfunction in Anorexia Nervosa. Abstract: A systematic review was implemented according to PRISMA guidelines on Pubmed, Psychinfo, Medline, Embase to fill the existing literature gap on the effectiveness of using Positron Emission Tomography (PET) and Single Photon Emission Computed Tomography (SPECT) in Anorexia Nervosa (AN), Bulimia Nervosa (BN) and Binge Eating Disorder (BED). Twenty-two articles were included. Four studies reported an increased density in 5-hydroxytryptamine receptor (5-HT1A ) in fronto-temporo-parietal regions in both affected and recovered AN as well as in BN. The 5-HT transporter (5-HTT) binding was increased or diminished in different specific cortical areas and in relation to Eating Disorder (ED) subtypes. Some evidences of blunted Dopamine (DA) release in the putamen in BN patients suggest that their DA function might be impaired as in addictive behaviours. Studies estimating the regional Cerebral Blood Flow (rCBF) with SPECT demonstrated that temporal areas seem to play a key role in ED corroborating the hypothesis of a cingulate-temporal cortical dysfunction in AN. In addition, alterations of both parietal and prefrontal cortex provide a possible common neural substrate in AN. Studies included in this review are heterogeneous preventing robust conclusions, however, our findings add knowledge on some of the neurotransmitters involved in ED.